Heckscher-Ohlin Trade Theory with a Continuum of Goods - Dornbusch, Rudiger; Fischer, Stanley; Samuelson, Paul A. (Quarterly Journal of Economics, 1980)
This paper studies trade theory for the case of a continuum of goods, two factors, two countries, and Cobb-Douglas demand functions. If factor endowments are similar, factor price equalization obtains and geographic patterns of production are indeterminate; nonetheless the effects of changes in factor endowments on prices and welfare in each country are well defined. Factor price equalization does not obtain if factor endowments are far apart, and the geographic pattern of specialization is then determinate. The effects of changes in endowments on the range of goods produced in each country and on prices of goods and factors are analyzed for this case, and the elasticity of substitution in production is shown to play an important role in determining comparative static outcomes.